THE INFLUENCE OF BUDGET PARTICIPATION AND ORGANIZATIONAL COMMITMENT TO MANAGERIAL PERFORMANCE (Case Study at PT. Adhi Karya Persero Tbk) - Dewi, Maya Widyana; Ningsih, Suhesti (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2020)
This study aims to examine the effect of budgeting and organizational commitment on managerial performance. The data collection of this study using questionnaires, as many as 70 questionnaires filled out completely and can be processed. Data were analyzed using descriptive statistical tests, validity and reliability tests, while hypothesis testing used multiple linear regression tests, t tests, F tests and the coefficient of determination (R2). The results showed that budgetary participation variables had a significant effect on managerial performance. The higher employee participation the higher the level of managerial performance. The variable organizational commitment has a significant effect on managerial performance. Thus the higher one's commitment to the organization, the higher the level of managerial performance. From the F test the variable budget participation and organizational commitment together (simultaneously) significantly influence managerial performance with the percentage of influence of 69.2% and the remaining 30.8% influenced by other variables outside this study Keywords: Budget Participation, Organizational Commitment, Managerial Performance